2019
DOI: 10.1186/s12885-019-5480-0
|View full text |Cite
|
Sign up to set email alerts
|

Malignant tumours in urban Ghana: evidence from the city of Kumasi

Abstract: BackgroundData from population-based cancer registries (PBCRs) are a useful resource for estimating the incidence of cancers. PBCR data is useful in the planning and implementation of cancer prevention and control strategies. Ghana’s plan for control of non-communicable diseases recognises the need for good quality data to facilitate the attainment of set goals.MethodsWe reviewed data from the Kumasi Cancer Registry for the year 2015. Data collected included clinical and demographic information, laboratory rep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
31
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(32 citation statements)
references
References 21 publications
1
31
0
Order By: Relevance
“…In Ghana, breast cancer is becoming a great public health challenge among women. With about 2,900 incident cases occurring annually, and one-eighth of them dying from it, the disease has become the most common cancer-related death among Ghanaian women [ 5 , 6 ]. Previous studies have revealed an increased breast cancer burden in Ghana over the past decade.…”
Section: Introductionmentioning
confidence: 99%
“…In Ghana, breast cancer is becoming a great public health challenge among women. With about 2,900 incident cases occurring annually, and one-eighth of them dying from it, the disease has become the most common cancer-related death among Ghanaian women [ 5 , 6 ]. Previous studies have revealed an increased breast cancer burden in Ghana over the past decade.…”
Section: Introductionmentioning
confidence: 99%
“…In Ghana, cervical cancer is ranked as the second most common cancer with an estimated incidence of 27.4 per 100,000 women [7,8]. Around 2797 women are diagnosed yearly and approximately 1699 deaths occur from cervical cancer [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…In Ghana, cervical cancer is ranked as the second most common cancer with an estimated incidence of 27.4 per 100,000 women [7,8]. Around 2797 women are diagnosed yearly and approximately 1699 deaths occur from cervical cancer [7,8]. The World Health Organization (WHO) predicts that there will be 5000 new cases of cervical cancer and 3361 cervical cancer deaths will occur annually in Ghana by 2025 [9].…”
Section: Introductionmentioning
confidence: 99%
“…An analysis of data from the WHO-Study on global AGEing and adult health (WHO-SAGE) waves 1 and 2, along with numerous other studies on different population groups, also revealed a rapid increase in the prevalence of overweightness and obesity among the Ghanaian adult population [46,47]. Similarly, the Performance and Accountability 2020 (PMA2020) surveys indicate that Ghana has one of the highest annual rates of modern contraceptive uptake in Africa [48].…”
Section: Discussionmentioning
confidence: 99%